Liquefaction Potential in the Adriatic Coastal Areas in Albania - Daja, Shkelqim; Ago, Besnik; Muci, Redi (Bulletin of the Geological Society of Greece, 2016)
The objective of this study is the evaluation of the phenomenon of liquefaction along the coastal area west of Albania. The study is based on the combination of qualitative approach which use geological criteria as the type of soil, their age, hydrogeological conditions and seismicity of the area and quantitative or deterministic approaches consisting on the evaluation of Liquefaction Potential Index (LPI). The quantitative analysis is based on the CPTU data. Three hazard levels, corresponding to different levels of safety such as 50% in 50 years (72-years Return Period), 10% in 50 years (475-years RP) and 2% in 50 years (2475-years RP), have been taken into consideration. The results of the deterministic approaches yielded further evidence of high potential of liquefaction, which suggests the same level of susceptibility for other ar-eas of the same geological conditions and stress history. These areas are mapped based on Geotechnical Map of Albania.